Competitive Performativity of (Academic) Social Networks. The subjectivation of Competition on ResearchGate, Google Scholar and Twitter - Stephan Pühringer; Georg Wolfmayr (Johannes Kepler University Linz, Research Project SPACE - Spatial Competition and Economic Policies, 2023)
This paper develops a better understanding of the explicit and implicit implications of the academic field's competitization, with a specific focus on the role that academic social networks and platforms (ASNPs) play in this process. By applying a mixed-methods approach combining a structural analysis and a questionnaire study, we compare ResearchGate, Google Scholar and Twitter and ask how and to what extent they contribute to the competitive subjectivation of their users. Therefore, we differentiate between suggested and enacted subjectivation, i.e., different levels of amplifying the self-perception of a 'competitive self.' We particularly find that ResearchGate, which is used by about two thirds of our respondents, offers a broad variety of tools for competitive subjectivation, yet all three ASNPs support the metric logic of individual research evaluation. Concerning differences in age, gender and disciplinary background, our results show that ASNPs are used more by younger and male researchers and these groups also perceive their work more competitively and act more competitively. While metric research evaluation is assessed as most important in the natural sciences and economics and rather unimportant in the humanities, social scientists especially perceive their work and their relation to colleagues in a competitive context.
Keywords: 330; academic social networks; competition; subjectivation; ResearchGate; Google Scholar; Austria